Interobserver agreement of semi-automated and manual measurements of functional MRI metrics of treatment response in hepatocellular carcinoma - Bonekamp, David (Eur J Radiol, 2013)
PURPOSE: To assess the interobserver agreement in 50 patients with hepatocellular carcinoma (HCC) before and 1 month after intra-arterial therapy (IAT) using two semi-automated methods and a manual approach for the following functional, volumetric and morphologic parameters: (1) apparent diffusion coefficient (ADC), (2) arterial phase enhancement (AE), (3) portal venous phase enhancement (VE), (4) tumor volume, and assessment according to (5) the Response Evaluation Criteria in Solid Tumors (RECIST), and (6) the European Association for the Study of the Liver (EASL). MATERIALS AND METHODS: This HIPAA-compliant retrospective study had institutional review board approval. The requirement for patient informed consent was waived. Tumor ADC, AE, VE, volume, RECIST, and EASL in 50 index lesions was measured by three observers. Interobserver reproducibility was evaluated using intraclass correlation coefficients (ICC). P < 0.05 was considered to indicate a significant difference. RESULTS: Semi-automated volumetric measurements of functional parameters (ADC, AE, and VE) before and after IAT as well as change in tumor ADC, AE, or VE had better interobserver agreement (ICC = 0.830–0.974) compared with manual ROI-based axial measurements (ICC = 0.157–0.799). Semi-automated measurements of tumor volume and size in the axial plane before and after IAT had better interobserver agreement (ICC = 0.854–0.996) compared with manual size measurements (ICC = 0.543–0.596), and interobserver agreement for change in tumor RECIST size was also higher using semi-automated measurements (ICC = 0.655) compared with manual measurements (ICC = 0.169). EASL measurements of tumor enhancement in the axial plane before and after IAT ((ICC = 0.758–0.809), and changes in EASL after IAT (ICC = 0.653) had good interobserver agreement. CONCLUSION: Semi-automated measurements of functional changes assessed by ADC and VE based on whole-lesion segmentation demonstrated better reproducibility than ROI-based axial measurements, or RECIST or EASL measurements.